Comportamiento de la familia Rallidae como indicador biológico en relación a la actividad camaronera en el Humedal La Segua - Cedeño Alcívar, José Alejandro (2022)
La Segua wetland is home to several families of aquatic avifauna, among them the Rallidae family, there are also shrimp farms whose activity generates impacts on the habitat of these species, which is why the objective of this research was to evaluate the behavior of the Rallidae family in relation to shrimp farming activity, the study area was georeferenced with the use of a drone, the methods used were statistical, deductive, inductive, analytical and bibliographic; the information was collected in situ through the application of surveys to the inhabitants; for the calculation of these data. Non-probabilistic sampling was used to measure the behavior of the birds, using the focal method. The impact of shrimp farming in the study area was evaluated using the Leopold cause-effect matrix. A total of 313 people were surveyed, 54% of whom stated that they had been involved in aquaculture for more than 15 years; in fact, 75 shrimp farms were identified. A total of six species of the Rallidae family were identified in the study area, with the common moorhen being the species with the highest number of individuals (63.73%) with a low diversity index. In addition, the Leopold matrix showed that there were 116 positive impacts and 196 negative impacts, concluding that shrimp farming activities negatively affect the behavior of the Rallidae, since their negative effects have repercussions on their natural environment.